Khoa học Luật hành chính với vấn đề đổi mới quản lý nhà nước ở Việt Nam trong giai đoạn hiện nay - Khải, Phạm Tuấn (VNU Journal of Science: Social Sciences and Humanities; Vol 15 No 2, 1999)
The author analyzes content, formality of reform of administration; effect of science of administrative law to entire state body in general and administration body in particular. The author points out the directions, views and measures in order to upgrade the effectiveness of administration and to strengthen the excution of regulations of administrative law in the process of renovation in Vietnam.